Impact of corporate social responsibility on corporate sector - G, Silpa Monica Chandran (Journal of Management and Science, 2022)
This paper gives a view on how companies enriched the brand Value, different innovations, and being competitive in the market through CSR. Corporate social responsibility is the main concept in the present business, especially in the corporate sector.CSR gained great importance because of the growing interest of people on social and environmental factors. Many companies have changed their working pattern by implementing corporate social responsibility. India is the first country that follows CSR legally and made a regulation in the constitution under the company’s act 2013. The government also initiates employee involvement,the contribution of companies for the promotion of CSR. Implementation of CSR in the corporate sector has witnessed remarkable changes towards social and economic factors. Even with the Globalization of the Indian Economy, CSR practices are evolving faster in India by Balancing economic, social, and environmental imperatives.